CONTESTED WATERS, CONTESTED FUTURES: THE SOUTH CHINA SEA SECURITY COMPLEX AND MALAYSIA'S SABAH DILEMMA - A Muruga Subramaniam, Gayathri; Fernandez, Kevin (AEI Insights, 2025)
Non-traditional security risks, including smuggling, human trafficking, arms proliferation, and kidnapping-for-ransom (KFR), are highly concentrated in Sabah due to its strategic location along the Tri-Border Area (TBA) and the Sulu Sea. These threats are further exacerbated by regional geopolitical tensions. Porous maritime borders, limited intelligence sharing, and evolving transnational crime networks continue to challenge Malaysia’s enforcement measures, despite initiatives such as the Eastern Sabah Security Command (ESSCOM) and ASEAN-led security frameworks. Applying the Regional Security Complex Theory (RSCT), this paper examines how multilateral cooperation, external geopolitical pressures, and regional interdependencies shape Malaysia’s security governance. Findings indicate that a unilateral approach is insufficient, necessitating enhanced maritime surveillance, stronger regional security cooperation, and socioeconomic strategies to address the root causes of crime. By integrating security enforcement with sustainable development and regional diplomacy, Malaysia can strengthen its governance in Sabah and reinforce its role as a key security actor in Southeast Asia.